Sistema On line para la gestión de ventas del local comercial Isabelita en la ciudad de Guaranda. - Aldas Aldaz, Juan Carlos (2025)
The project automates sales management for the Isabelita store in Guaranda, overcoming the limitations of manual processes that negatively impacted decision-making and business competitiveness. An information system was implemented based on controlled development models to ensure quality and scalability. The Scrum agile methodology was used for development, enabling rapid construction and close collaboration with the client. Data collection tools facilitated the identification of essential requirements for designing an efficient and functional application. The system was designed using the Model-View-Controller (MVC) architecture, separating business logic from presentation logic, which promotes scalability and maintainability. PostgreSQL was employed as the database management system, ensuring robust and secure management of key information such as sales, customers, products, and suppliers. The software development utilized JavaScript, leveraging Node.js for the backend and React.js for creating dynamic and interactive web interfaces. As a result, the system significantly reduced sales registration time, improved inventory accuracy, and optimized customer service. The project concludes with recommendations to maximize the benefits of the implemented system, achieving the proposed objectives and enhancing business management.